SYSTEMATIC LITERATURE REVIEW: PENGGUNAAN AUGMENTED REALITY DALAM PEMBELAJARAN FISIKA DI SEKOLAH DASAR - Novriandi; Hafizul; Devira Syafitri Amizi; Azizah Nurazila; Ena Suma Indrawati; Lelfita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to systematically examine the use of Augmented Reality (AR) in elementary school physics learning through a Systematic Literature Review (SLR) approach. The review was conducted on scholarly articles published between 2015 and 2025 and retrieved from the Google Scholar database. The SLR method followed the PRISMA framework, which includes the stages of identification, screening, eligibility, and inclusion of articles. The findings indicate that AR consistently contributes to improving students’ conceptual understanding of physics, learning motivation, and engagement, particularly in abstract subject matter. However, the implementation of AR still faces challenges related to limited infrastructure and teachers’ digital pedagogical competencies. The results of this study are expected to serve as both a theoretical and practical reference for the development of technology-based physics learning in elementary schools.